Correlation of Electrophysiological and Gene Transcriptional Dysfunctions in Single Cortical Parvalbumin Neurons After Noise Trauma. (1st February 2022) - Wang, Weihua; Deng, Di; Jenkins, Kyle; Zinsmaier, Alexander K.; Zhou, Qiang; Bao, Shaowen
Highlights: Noise-induced hearing loss leads to reduced expression of PV, GAD65/67, and KV3.1. PV expression in single neurons is correlated with GAD67 but not KV3.1 expression. Spike frequency adaptation increases following noise-induced hearing loss. Spike frequency adaption is correlated with KV3.1, but not PV or GAD67, expression. Abstract: Parvalbumin-expressing (PV+) interneurons in the sensory cortex form powerful inhibitory synapses on the perisomatic compartments and axon initial segments of excitatory principal neurons (PNs), and perform diverse computational functions. Impaired PV+ interneuron functions have been reported in neural developmental and degenerative disorders. Expression of the unique marker parvalbumin (PV) is often used as a proxy of PV+ interneuron functions. However, it is not entirely clear how PV expression is correlated with PV+ interneuron properties such as spike firing and synaptic transmission. To address this question, we characterized electrophysiological properties of PV+ interneurons in the primary auditory cortex (AI) using whole-cell patch clamp recording, and analyzed the expression of several genes in samples collected from single neurons using the patch pipettes. We found that, after noise induced hearing loss (NIHL), the spike frequency adaptation increased, and the expression of PV, glutamate decarboxylase 67 (GAD67) and Shaw-like potassium channel (KV3.1) decreased in PV+ neurons. In samples prepared from the auditory cortical tissue, the mRNA levels of the target genes were all pairwise correlated. At the single neuron level, however, the expression of PV was significantly correlated with the expression of GAD67, but not KV3.1, maximal spike frequency, or spike frequency adaptation. The expression of KV3.1 was correlated with spike frequency adaptation, but not with the expression of GAD67. These results suggest separate transcriptional regulations of PV/GAD67 vs. KV3.1, both of which are modulated by NIHL.